EVALUASI PENGALAMAN PENGGUNAAN TEKNOLOGI KECERDASAN BUATAN (ARTIFICIAL INTELLIGENCE) PADA INDUSTRI PERBANKAN: MIXED METHODS - Mahdi, Sayed; -, Safriatullah; Jais, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study explores user experience in adopting artificial intelligence (AI) in Indonesia's banking industri through a mixed-methods approach, emphasizing qualitative insights from user interactions. Findings show that user trust is the key faktor in AI adoption, influenced by perceived usefulness, security, ease of use, and personalization, which together shape satisfaction and continued usage. Five key themes emerged: trust and security, quality of interaction and personalization, simplicity of interface, performance alignment with expectations, and the importance of user education and support. The study highlights that user engagement with AI goes beyond technical aspects, involving emotional and cognitive perceptions such as safety and control. To successfully integrate AI, banks must adopt a holistic approach that combines technological advancement with transparency, user empowerment, and data privacy. This research refines the technology adoption framework by adding human-centered dimensions and offers actionable insights for banks, developers, and policymakers in Indonesias financial sector.